2012
DOI: 10.1039/c2jm33856d
|View full text |Cite
|
Sign up to set email alerts
|

A simple and high-effective electrolyte mediated with p-phenylenediamine for supercapacitor

Abstract: A redox intermedium p-phenylenediamine (PPD) with quick reversible faradaic processes is introduced into KOH electrolyte, referred to as pseudocapacitive effect occurring on the electrode/electrolyte surface. The KOH + PPD electrolyte as potential electrolyte for supercapacitors is investigated by UV-Vis spectroscopy and electrochemical methods. As expected, the supercapacitor with KOH + PPD electrolyte has a much higher electrode specific capacitance (605.225 F g À1 ) than the one with conventional KOH electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(82 citation statements)
references
References 35 publications
(34 reference statements)
2
80
0
Order By: Relevance
“…This results indicated that the redox reaction of molybdic acid (H 2 MoO 4 ) at the electrode|electrolyte interface largely improved the specific capacitance of carbon based supercapacitors (the conclusion is consistent with the current literature depiction [11,25,45]), which will be further substantiated by the following galvanostatic charge-discharge technique. In addition, it is noticeable that the background signal based on bare glassy carbon (GC) electrode in mixed 1 M H 2 SO 4 and 0.06 M Na 2 MoO 4 electrolyte (system 3) are negligible from the CV curves in Fig.…”
Section: Electrochemical Characterization Of Ac Electrodes In Redox-msupporting
confidence: 88%
See 1 more Smart Citation
“…This results indicated that the redox reaction of molybdic acid (H 2 MoO 4 ) at the electrode|electrolyte interface largely improved the specific capacitance of carbon based supercapacitors (the conclusion is consistent with the current literature depiction [11,25,45]), which will be further substantiated by the following galvanostatic charge-discharge technique. In addition, it is noticeable that the background signal based on bare glassy carbon (GC) electrode in mixed 1 M H 2 SO 4 and 0.06 M Na 2 MoO 4 electrolyte (system 3) are negligible from the CV curves in Fig.…”
Section: Electrochemical Characterization Of Ac Electrodes In Redox-msupporting
confidence: 88%
“…Su [11]. Similarly, carbon based capacitance of 144.037 F g -1 (2 M KOH) was raised to 605.225 F g -1 via introducing p-phenylenediamine in 2 M KOH [25]. Based on these reports it can be concluded that the redox additives or compounds can increase the original capacitance of the supercapacitor material by two-to four-fold.…”
Section: Introductionmentioning
confidence: 95%
“…An innovative approach to supercapacitors has recently been developed by the introduction of a single redox additive such as hydroquione [23][24][25], methylene blue [26],p-phenylenediamin [27,28], m-phenylenediamine [29], indigo carmine [30], KI [31][32][33], Na 2 MO 4 [34] or VOSO 4 [35] into the liquid electrolyte or GPE. The specific capacitance and energy density of the supercapacitor are greatly increased as a result of the additional pseudocapacitance deriving from the electron transfer redox reaction of the redox additive.…”
Section: Introductionmentioning
confidence: 99%
“…1) intensifies the electron transfer in the midst of NC-TEG electrode and KOH electrolyte, leading to a direct increase in capacitive performance [35]. The combination of redox pseudo-capacitive electrolyte mediator and the EDL effective electrodes induced a synergic capacitive increase in the charge-discharge process.…”
mentioning
confidence: 98%